Vocational Education in the Covid-19 Pandemic: Issues and Recommendation - Beata Jakimiuk (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: The Covid-19 pandemic has changed the teaching and functioning of schools at every stage of education. New challenges, difficulties, problems and experiences have appeared, which particularly affected vocational schools due to the way practical training could be implemented. Research Aim: The purpose of the study was to show how vocational schools, headmasters, and vocational teachers coped with their tasks during the COVID-19 pandemic and how the quality of vocational education changed. Method: Qualitative strategy - factual interview with elements of conceptual interview. Results: The research revealed the complications experienced by headmasters and teachers in teaching theoretical and practical vocational subjects, organizing internships and vocational exams, as well as their ways of coping with difficulties. Conclusion: Remote education in vocational schools requires both financial and systemic support; in particular, the availability of right hardware and software, training, funds to recruit educators teaching vocational subjects, as well as cooperation with employers as integral part of vocational education.